Reptiles - Berger, Melvin. frey50; Berger, Gilda (New York : Scholastic, 2008)
Asks readers a true-or-false question about the physical characteristics, diet, or behavior of reptiles that the reader can find the answer to by turning the page.
Includes index.
Keywords: Reptiles; Reptiles